Brief communication: Collapse of 4Mm3 of ice from a cirque glacier in the Central Andes of Argentina - Falaschi, Daniel (2019)
Among glacier instabilities, collapses of large parts of low-angle glaciers are a striking, exceptional phenomenon. So far, merely the 2002 collapse of Kolka Glacier in the Caucasus Mountains and the 2016 twin detachments of the Aru glaciers in western Tibet have been well documented. Here we report on the previously unnoticed collapse of an unnamed cirque glacier in the Central Andes of Argentina in March 2007. Although of much smaller ice volume, this 4:2 ± 0:6 × 106 m3 collapse in the Andes is similar to the Caucasus and Tibet ones in that the resulting ice avalanche travelled a total distance of ∼ 2 km over a surprisingly low angle of reach (∼ 5°).